Bankruptcy Verdict as a Legal Result of the Rejection of the Peace Plan Proposal by Creditors in the Process of Postponing Debt Repayment Obligations (PKPU) - Mulyanta Sembiring, Dedek; Sitompul, Ariman; Sahputra, Rilawadi; Azmi, Syariful (International Asia Of Law and Money Laundering, 2024)
The process of postponing the debt payment obligation (PKPU) lasts for 270 (two hundred and seventy) days starting from the reading of the PKPU decision. Within 270 days the debtor must prepare a peace plan in the form of a peace proposal that will be offered to the creditors to repay its debts. The peace plan or often referred to as the peace Proposal plan is not clearly regulated and detailed in Law Number 37 of 2007 on bankruptcy and delay and debt repayment obligations. The peace plan is one of the debtor's efforts to make payments on debts that have been registered by creditors, verified and recognized by the debtor which is then authorized by the supervisory judge through the establishment of a fixed Bill list. The peace plan will not necessarily be accepted by the creditors but there will be discussion and voting that will determine whether or not the peace plan offered by the debtor is accepted as a determinant of whether PKPU will end with a bankruptcy decision will be handed down or homologation decision. The method of research conducted in this writing is to use the normative method. This study was conducted by searching and understanding the literature or the bankruptcy law and debt repayment obligation postponement (PKPU) with literature research. This study will examine how the process of postponement of debt repayment obligations (PKPU) until the bankruptcy verdict is handed down to the debtor based on the study of the Commercial Court decision at the Semarang District Court Number : 9/Pdt.Sus-PKPU/2024 / PN.Commerce.Smg). Thus, it can be seen how the process of discussing the peace plan proposal in the process of postponing debt payment obligations (PKPU) will determine whether the bankruptcy decision will be imposed on the debtor or the Peace decision (homologation).